2018
DOI: 10.1007/s10735-018-9775-2
|View full text |Cite
|
Sign up to set email alerts
|

CGRP gene-modified rBMSCs show better osteogenic differentiation capacity in vitro

Abstract: Calcitonin gene-related peptide (CGRP) is a marked and important neuropeptide expressed in nerve fibers during bone repair. This study investigated the role of CGRP overexpression on osteogenic differentiation of rat bone mesenchymal stem cells (rBMSCs). rBMSCs were infected with viral stocks of pLenO-DCE-CGRP (CGRP group) or pLenO-DCE (Vector group), while normal rBMSCs were used as a control. Transfection efficiency of rBMSCs was analyzed by flow cytometry. Cell proliferation was examined using a Cell Counti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…Genetically modified stem cells have been shown to play significant roles in promoting bone regeneration [5]. Previous studies have reported that a variety of factors, such as transcription factors, growth factors, cytokines, and extracellular matrix molecules, can promote osteogenesis and angiogenesis in bone tissue engineering [6].…”
Section: Introductionmentioning
confidence: 99%
“…Genetically modified stem cells have been shown to play significant roles in promoting bone regeneration [5]. Previous studies have reported that a variety of factors, such as transcription factors, growth factors, cytokines, and extracellular matrix molecules, can promote osteogenesis and angiogenesis in bone tissue engineering [6].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis on the interaction network of candidate genes by the GeneMANIA tool indicated that six genes had higher interaction scores, including DMP1 (score = 0.867194116), SOST (score = 0.814230232), SP7 (score = 0.786778992), IBSP (score = 0.758063414), MEN1 (score = 0.737518121), and CALCA (score = 0.733867971) ( Figure 2(b) ). Existing evidence has confirmed the correlation between CGRP and osteogenic differentiation of hPDLSCs [ 19 , 20 ]. CGRP was also predicted to be upregulated in the GSE53929 dataset ( Figure 2(c) ).…”
Section: Resultsmentioning
confidence: 79%
“…4 In vitro, CGRP may regulate bone metabolism by inhibiting osteoclast formation, 8 whereas studies have shown that CGRP can promote bone mesenchymal stem cell osteogenic differentiation and osteogenic ability linked to the higher expression of osteogenesis-related indexes alkaline phosphatase, bone sialoprotein, and runt-related transcription factor 2. 13,35 Recombinant human CGRP can induce rabbit adipose-derived stem cells into osteoblast differentiation. 11 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%